Nutritional status, Mediterranean diet adherence, and quality of life in older adults with dementia: A cross-sectional study - Sessiz Menekse, Ezgi Barin; Bayraktar, Damla Zeynep; Cevik, Mehmet Ugur; Menekse, Velat; Elmas, Negin (Sage Publications Ltd, 2026)
Background: Nutritional problems are common among individuals living with dementia and may adversely affect quality of life. While the Mediterranean diet has been widely studied in dementia prevention, evidence regarding its role after dementia diagnosis remains limited. Objective: This study aimed to evaluate the relationship between nutritional status, adherence to the Mediterranean diet, and quality of life among older adults with dementia. Methods: This cross-sectional study was conducted with 150 older adults diagnosed with dementia. Data were collected using the Mini Nutritional Assessment (MNA), the Mediterranean Diet Adherence Screener (MEDAS), and the WHOQOL-OLD Quality of Life Questionnaire. Results: Participants generally demonstrated moderate adherence to the Mediterranean diet (mean MEDAS 9.4 +/- 2.4). Mediterranean diet adherence was not significantly associated with nutritional status or quality of life. In contrast, nutritional status showed a significant and independent positive association with quality of life after adjustment for potential confounders. In multiple linear regression analysis, MNA score remained a significant predictor of quality of life (beta = 0.28, p = 0.002). Conclusions: In older adults with dementia, nutritional status is independently associated with quality of life, whereas adherence to the Mediterranean diet shows no significant relationship with nutritional status or quality of life in this cross-sectional sample. These findings highlight the importance of routine nutritional assessment and individualized nutritional support in dementia care.
Keywords: Alzheimer's disease; cognitive functions; dementia; malnutrition; Mediterranean diet; quality of life